Competing Global and Local Halal Standards: Indonesia's Strategy in Increasing Halal Food Exports After Ratifying SMIIC - Hakim, Moh. Fathoni; Amaliyah, Ridha (Journal of Digital Marketing and Halal Industry, 2024)
This study examines the obstacles and strategies for Indonesia in harmonizing the global halal standards of SMIIC (The Standards and Metrology Institute for Islamic Countries) to enhance halal food exports to OIC (Organization of Islamic Cooperation) member countries. Using a descriptive qualitative approach, data were collected through observations, interviews with halal stakeholders, and documentation. The findings reveal several barriers to harmonization, including the voluntary nature of SMIIC standards, the fact that approximately 35% of OIC countries have not joined SMIIC, and differences in Islamic schools of thought among member countries. Additional challenges include internal constraints, such as the classification of many OIC countries as Least Developed Countries (LDCs), the dominance of halal food suppliers from non-Muslim countries, and market protection policies. To address these challenges, Indonesia has adopted a localization strategy by establishing Mutual Recognition Arrangements (MRAs) with foreign halal certification bodies. By the end of 2024, Indonesia aims to achieve 92 MRAs, which act as a "middle ground" between global and local halal standards and have proven effective in increasing halal food exports to OIC member countries. The implications of this study highlight MRAs as a viable policy model for balancing local and global interests while strengthening Indonesia's economic ties with Muslim nations. This strategy demonstrates that standard localization within a global framework offers a pragmatic solution to the challenges of halal harmonization, thereby reinforcing Indonesia's role in the international halal market.